Green synthesis of ZnO nanorods using Cassia fistula flower extract: characterization and antibacterial activity - Prateeksha Sharma; Nupur Aggarwal; Naveen Kumar (Discover Materials)
Abstract Green route-synthesized metal oxide nanostructures have emerged as promising candidates for antimicrobial applications due to their eco-friendly, cost-effective, and sustainable nature. The present report displays a cost-effective, safe, and environmentally benign method to synthesize zinc oxide (ZnO) nanorods (NRs) using aqueous flower extract of Cassia fistula. The crystallinity of Cassia fistula flower extract-mediated zinc oxide nanorods (CFFE@ZnO NRs) was estimated using the X-ray diffraction (XRD) method, and it was observed that CFFE@ZnO NRs possess a hexagonal crystalline structure with $$\:P{6}_{3}mc$$ space group. Microstructural analysis revealed that CFFE@ZnO NRs exhibit nanorod-like morphology and Selected area electron diffraction (SAED) image displayed concentric rings belonging to Miller planes (002), (100), and (111) belonging to hexagonal symmetry, thereby confirming the phase pure synthesis. The UV-visible spectrum of CFFE@ZnO NRs possessed a characteristic absorption peak at 327 nm with an optical energy band gap ( $$\:E_{g}$$ ) of 3.31 eV. The TGA/DTA curves demonstrated that CFFE@ZnO NRs maintain thermal stability with a transition temperature of 393 °C. CFFE@ZnO NRs exhibited antibacterial properties against gram-positive bacteria, including Staphylococcus aureus and Bacillus subtilis, as well as gram-negative bacteria, such as Escherichia coli and Salmonella typhi. This study underscores the physicochemical characteristics of CFFE@ZnO NRs and their potential as antibacterial agents for various applications.